2008
DOI: 10.1093/gerona/63.12.1289
|View full text |Cite
|
Sign up to set email alerts
|

Airspace Enlargement With Airway Cell Apoptosis in Klotho Mice: A Model of Aging Lung

Abstract: Homozygous mutant klotho (KL(-/-)) mice exhibit various characteristics resembling those of human aging, including emphysema. However, age-related changes of lungs have not been fully elucidated. Here, we investigated the structural, functional, biochemical, and cell kinetic alterations of lungs in KL(-/-) mice at 2-12 weeks of age. Homogeneous airspace enlargement and decreased lung elastic recoil were observed in KL(-/-) mice with aging. The apoptotic cells in airway walls in KL(-/-) mice were approximately … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 37 publications
3
25
0
1
Order By: Relevance
“…These data are among the earliest KO reported changes. Other 3 week KO studies found increased serum Vitamin D (Yoshida et al 2002; Tsujikawa et al 2003), increased skin wnt reporter activation (Liu et al 2007), and increased lung apoptotic and proliferative indexes (Ishii et al 2008). Since skin and lung do not express KL (Kuro-o et al 1997), these data implicate the importance of shed KL.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…These data are among the earliest KO reported changes. Other 3 week KO studies found increased serum Vitamin D (Yoshida et al 2002; Tsujikawa et al 2003), increased skin wnt reporter activation (Liu et al 2007), and increased lung apoptotic and proliferative indexes (Ishii et al 2008). Since skin and lung do not express KL (Kuro-o et al 1997), these data implicate the importance of shed KL.…”
Section: Discussionmentioning
confidence: 93%
“…KL HET mice show decreased freezing consistent with cognitive impairment 24 hours after training, although impairment was less pronounced than KO mice (Figure 6C). Although KL heterozygotes do not develop the severe symptoms of loss of KL from renal systems (Kuro-o et al 1997), they do display lung and heart abnormalities most likely resulting from decreased shed KL (Suga et al 2000; Sato et al 2005; Ishii et al 2008). Meanwhile, consistent with the previous report (Dubal et al 2014), 6 month OE mice froze more than WT (Figure 6D).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, one animal displayed a particular phenotype resembling aging, caused by the insertional mutation of the transgene in the promoter region of what will be later identified as the Klotho gene. The homozygous animals for the inserted transgene had a shorter life span and precociously developed pathologies related to aging including osteoporosis (86), hypogonadotropic hypogonadism, arteriosclerosis, skin atrophy, pulmonary emphysema (78, 169), neurodegenerative (5, 146), and auditory syndromes (84, 197). …”
Section: Fgf23 Functionmentioning
confidence: 99%
“…Mice defective in klotho gene expression develop multiple aginglike phenotypes around 3-4 weeks after birth, including growth retardation, hypogonadotropic hypogonadism, rapid thymus atrophy [33], skin atrophy, sarcopenia, vascular calcification, osteopenia [34], pulmonary emphysema [35][36][37], cognition impairment [38], hearing disturbance [39], and motor neuron degeneration [40], and die around 2 months of age. In contrast, transgenic mice that overexpress Klotho live longer than wild-type mice [41].…”
Section: Klothomentioning
confidence: 99%